Glycoproteomic analysis and molecular modeling of haptoglobin multimers - Boonyapranai K. (2014)
Extra-thiol groups on the α-subunit allow haptoglobin (Hp) to form a variety of native multimers which influence the biophysical and biological properties of Hp. In this work, we demonstrated how differences of multimeric conformation alter the glycosylation of Hp. The isoform distributions of different multimers were examined by an alternative approach, i.e. 3-D-(Native/IEF/SDS)-PAGE, which revealed differences in N-glycosylation among individual multimers of the same Hp sample. Glycomic mapping of permethylated N-glycan indicated that the assembled monomer and multimeric conformation modulate the degree of glycosylation, especially the reduction in terminal sialic acid residues on the bi-antennary glycan. Loss of the terminal sialic acid in the higher order multimers increases the number of terminal galactose residues, which may contribute to conformation of Hp. A molecular model of the glycosylated Hp multimer was constructed, suggesting that the effect of steric hindrance on multimeric formation is critical for the enlargement of the glycan moieties on either side of the monomer. In addition, N241 of Hp was partially glycosylated, even though this site is unaffected by steric consideration. Thus, the present study provides evidence for the alteration of glycan structures on different multimeric conformations of Hp, improving our knowledge of conformation-dependent function of this glycoprotein. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.